Comparative Public Policy Analysis: Shortcomings, Pitfalls, and Avenues for the Future - Georg Wenzelburger; Carsten Jensen (Politische Vierteljahresschrift, 2022)
Comparative public policy is a~blooming research area. It also suffers from some curious blind spots. In this paper we discuss four of these: (1)~the obsession with covariance, which means that important phenomena are ignored; (2)~the lack of agency, which leads to underwhelming explanatory models; (3)~the unclear universe of cases, which means the inferential value of theories and the empirical results are unclear; and (4)~the focus on outputs, even though most theories contain strong assumptions about the political process leading to certain outputs. Following this discussion, we then outline how a~closer integration of policy process theories may be fruitful for future research.
Keywords: 320; Comparative; Public policy; Comparative political economy; Policy process; Quantitative methods; Vergleichende Policy-Forschung; Staatstätigkeit; Policy-Prozess; Quantitative Methoden